A comparative study on the process efficiencies and microbial community structures of six full-scale wet and semi-dry anaerobic digesters treating food wastes. (December 2017) - Han, Gyuseong; Shin, Seung Gu; Lee, Joonyeob; Shin, Juhee; Hwang, Seokhwan
Highlights: Wet digesters showed a higher process efficiency than semi-dry digesters. Bacterial and archaeal communities were distinctly characterized by key families. TS content, [TAN], and SCOD/COD in the digester were the discriminant parameters. Abstract: The purpose of this study was to investigate the effect of different types of food wastes on the process efficiency and microbial community structures in full-scale anaerobic digesters and to identify parameters that affect these criteria. Six full-scale anaerobic digesters were investigated; three were operated under "wet" condition (total solids TS ≤ 10%), and three were run under "semi-dry" condition (10% ≤ TS ≤ 20%). Removal efficiency of volatile solids was much higher in the wet digesters (75.2 ± 3.8%) than in the semi-dry digesters (42.6 ± 5.5%). The bacterial and archaeal communities were distinctly characterized by families Porphyromonadaceae, Sphingobacteriaceae, Syntrophomonadaceae, and Methanobacteriaceae in the wet digesters; and of Clostridiaceae, Patulibacteraceae, Pseudonocardiaceae, Lachnospiraceae, Rikenellaceae, and Methanomicrobiaceae in the semi-dry digesters. The discriminant parameters identified were TS content of influent, concentration of total ammonia nitrogen and the ratio of soluble chemical oxygen demand (COD) to COD in the digester.